Zakat Management Strategy in Poverty Alleviation: Study of Zakat Collecting Institutions in Indonesia - Engkos Koswara (GoAcademica Research & Publishing, 2020)
In Islam, one of the efforts to overcome poverty is through zakat. Therefore, zakat must be managed professionally and professionally, so zakat can be taken part in realizing Islamic ideas for the welfare of society. one of the institutions that are proven capable of managing zakat that is trusted, transparent, and professional is Rumah Zakat Indonesia (RZI). This study aims to describe the management of zakat conducted by Rumah Zakat Indonesia in alleviating poverty through community empowerment. Using socio-economics, and interpreting it into a form of complete research information.